Mabadi’ Asyroh Nalar Fikih Sosial Ali Yafie - Y Yulianto (UIN Raden Mas Said Surakarta, 2017)
Making a decision in Islamic law must be contextual and give a priority to umma’s benefit (mashlahat) and consider a sense of justice. This purpose portrays the main thought of Ali Yafie’s social fiqh. This research uses a descriptive qualitative method to see social fiqh. The result of this research shows that Ali Yafie’s social fiqh thought by taking mabadi’ asyroh (ten principles) which are: (1) hadul ilmi is methodological process and product of legislation of Islamic law; (2) maudlu’ul ilmi is identification of social problems; (3) tsamrotul ilmi is umma’s benefits; (4) fadlul ilmi is obligation of each Moslem; (5) nisbatul ilmi is maqashid al-syariah and fardlu ‘ain- fardlu kifayah considerations; (6) wadli’ul ilmi is KH. A. Sahal Mahfudz dan K.H. Ali Yafie, (7) ismul ilmi is social fiqh, (8) istimdadul ilmi is Alquran, hadith, al-ijma’, qiyas, rational-holistic integration, reality, and interpreting Islamic texts based on social benefits (mashlahah), (9) hukmul ilmi is wajib kifayah and wajib ‘ain, and (10) masailul ilmi, is any social problems.